Exploring Hiring Practitioner Preferences for and Assessment Practices of Prospective Candidates. Issue 4 (December 2018) - Huber, Amy
While the decision–making strategies involved in the design process have long been a topic of scholarly exploration, less attention has been devoted to probing the likely antecedents to other decisions that potentially influence design practice. One such decision is the formation of a project team, which is likely influenced by those who are hired to work in a firm. While some interior design scholars have outlined the skills and characteristics viewed as most desirable by hiring practitioners, there remains relatively little information regarding the assessment of those attributes and how decision–making strategies may sway the hiring process. This study sought the perceptions of those hiring entry–level interior design candidates. More specifically, it aimed to determine preferences among the commonly cited factors of employability; namely, if hiring practitioners were more apt to prefer soft skills, hard skills, or specific experiences. The study then sought to discern whether those attributes are assessed through either System 1 (i.e., gut–level abbreviated processes often reliant on heuristics) or System 2 strategies (i.e., rational, conscious processes utilizing a broad array of evidence). Findings stemming from a survey of ( n = 106) senior–level interior design practitioners suggest that they are likely to prioritize soft skills when screening candidates. Moreover, practitioners may utilize System 1 processes, heuristics, and relatively subjective strategies—to assess these attributes. Findings offer practical implications while contributing to the body of knowledge regarding the employability of interior design university graduates by empirically examining how hiring practitioners prioritize of a range of cognitive, emotional, and behavioral patterns.